Doppler Color Scoring System in Women With an Incomplete Miscarriage: Interobserver and Intraobserver Reproducibility Study. (29th January 2019) - Leong, Grace Ting Ting; Leonardi, Mathew; Lu, Chuan; Mein, Brendan; Espada, Mercedes; Shakeri, Babak; Nadim, Batool; Reid, Shannon; Casikar, Ishwari; Condous, George
Abstract : Objectives: Doppler Color Scoring (DCS) has been used to predict successful expectant management of incomplete miscarriage. The aim of this study was to assess inter‐ and intraobserver reproducibility of the DCS system in women with incomplete miscarriage noted on transvaginal sonography. Methods: This was a prospective reproducibility study involving offline analysis of 32 prerecorded video sets on transvaginal sonography in real time of women with incomplete miscarriage. Vascularization of retained products of conception was recorded using the DCS system adopted from the International Ovarian Tumor Analysis group. Five gynecologic sonologists of varying experience assigned a DCS classification to each video in the analysis. The same videos were reanalyzed, in a different order, at least 7 days later, to assess intraobserver agreement. Inter‐ and intraobserver correlations were performed to determine agreement. Interobserver agreement was also measured between each observer and the reference standard (G.C.). A Cohen's κ coefficient value less than 0 suggests poor agreement, 0.01 to 0.20 slight, 0.21 to 0.40 fair, 0.41 to 0.60 moderate, 0.61 to 0.80 substantial, and 0.81 and 0.99 almost perfect. Results: Interobserver agreement for all observers for DCS allocation ranged from 0.480 to 0.751. Overall interobserver agreement for 5 observers was substantial (κ, 0.626). Overall interobserver agreements for the 2 inexperienced and 3 experienced observers compared to G.C. were 0.521 and 0.618, respectively. Experienced observers achieved overall almost perfect intraobserver agreement, compared to substantial agreement for inexperienced sonologists. Conclusions: DCS interobserver reproducibility between all observers and GC ranged from moderate to substantial. DCS intraobserver reproducibility was substantial to almost perfect. The DCS system appears to be a reproducible tool in evaluating women with incomplete miscarriage.